The connection between resistance training, climbing performance, and injury prevention - Saeterbakken, A. H.; Stien, N.; Pedersen, H.; Langer, K.; Scott, S.; Michailov, M. L.; Gronhaug, G.; Baláš, J.; Solstad, T. E. J.; Andersen, V. (Sports Medicine - Open, 2024)
Key Points